METAKOGNISI SISWA BERGAYA KOGNITIF FIELD-INDEPENDENT DALAM MEMECAHKAN MASALAH MATEMATIKA BERDASARKAN TAHAPAN POLYA - Afin Nur Latifa; Subanji Subanji; Erry Hidayanto (Jurnal Kajian Pembelajaran Matematika, 2020)
Metacognition is one important component in cognitive function and cognitive development that has a close relationship with students' problem solving abilities. One factor that can affect student metacognition but is rarely considered in mathematics learning is student cognitive style. The purpose of this study is to describe the metacognition of field-independent cognitive style students in solving mathematical problems based on Polya's stages. This research is a descriptive qualitative study using a problem solving test instrument and interview guidelines to collect data. The subjects in this study were 2 field-independent cognitive style students. The subject was asked to work on mathematical problem solving problems and then interviewed based on the results of student work. The results showed that students' metacognition awareness, regulation, and evaluation emerged during the problem solving stage. This shows that metacognition can help students with field-independent cognitive style in solving problems.